Analysis of Bigetron E-Sport Team Branding Strategy via the Instagram Platform - Alfin Imam Mahsus; Poppy Febriana (LPPM Stikosa - AWS, 2024)
This research aims to analyze the branding strategy used by the Bigetron E-Sport Team via the Instagram platform, with a focus on symbolic aspects of strategy, brand as a friend, nostalgia and event branding. The research method used is descriptive qualitative with data collection through non-participant observation of feed posts and reels from the @bigetronesports account. The theory used in this research refers to branding strategy concepts in the book